Determination of heparin-induced IgG antibody by fluorescence-linked immunofiltration assay (FLIFA) - Wang, Lianchun; Huhle, Günter; Malsch, Reinhard; Hoffmann, Ursula; Song, Xuehong; Harenberg, Job (Journal of immunological methods, 1999)
A fluorescence-linked immunofiltration assay (FLIFA) was developed for the determination of heparin-induced IgG in heparin-induced thrombocytopenia (HIT) type II patients. Protein A was immobilized on a nitrocellulose membrane to bind heparin-induced IgG of HIT type II patients. Fluorescein-5-isothiocynate (FITC)-heparin was added to platelet factor 4 present in normal serum to form the neo-antigen which was captured by heparin-induced IgG. The heparin-induced IgG was quantified by the relative fluorescence intensity (RFI) of bound FITC-heparin. Values were expressed as a RFI ratio (RFI patient / RFI normal) and were 1.965±0.413 in HIT type II patients (n=36) and 1.064±0.162 in healthy controls (n=50, p<0.0001). The intra- and inter-assay coefficients of variation were 4.9 and 10.4%, respectively. The heparin-induced IgG FLIFA will be useful in individual and epidemiological studies in patients during treatment with heparin. The FLIFA technique offers an alternative, rapid and sensitive methodological approach for studies on the interaction between antigen-antibody or ligand-receptor.